2022
DOI: 10.3390/v14102256
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Infants Less than 3 Months: Severe or Not Severe Disease?

Abstract: Compared to adults, severe or fatal COVID-19 disease is much less common in children. However, a higher risk for progression has been reported in infants. Different pediatric COVID-19 severity scores are reported in the literature. Methods: Subjects under 90 days of age admitted to 35 Italian institutions for COVID-19 were included. The severity of COVID-19 was scored as mild/moderate or severe/critical following the classification reported in the literature by Venturini, Dong, Kanburoglu, and Gale. To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 26 publications
4
32
0
Order By: Relevance
“…The majority of admitted neonates and children in this study were COVID-19-positive and without co-morbidities, similar to findings from Ghana, Italy and India [ 9 , 12 , 62 ]. In addition, children were typically admitted with moderate-to-severe disease rather than asymptomatic or mild disease.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of admitted neonates and children in this study were COVID-19-positive and without co-morbidities, similar to findings from Ghana, Italy and India [ 9 , 12 , 62 ]. In addition, children were typically admitted with moderate-to-severe disease rather than asymptomatic or mild disease.…”
Section: Discussionsupporting
confidence: 87%
“…Dona et al reported the outcomes of 216 infants less than 90 days old affected with COVID-19 disease from 35 Italian institutions. Only 2.3% of infants needed intensive care unit admission, and all infants recovered from the illness [ 27 ]. A population-based study from the UK reported 66 neonates with confirmed SARS-CoV-2 infection (incidence 5.6 per 10,000 live births) required hospital admission.…”
Section: Epidemiology Of Covid-19mentioning
confidence: 99%
“…The actual incidence of COVID-19 in neonates and infants continues to be underestimated, mainly due to asymptomatic cases and a lack of testing. Studies reporting higher morbidity and mortality in neonates and infants have not accounted for pre-existing comorbidities or used an arbitrary definition for diagnosing severe disease [ 27 ]. Epidemiologic data seems promising to propose that neonates and young children may continue to evade severe COVID-19 disease during the upcoming period.…”
Section: Epidemiology Of Covid-19mentioning
confidence: 99%
“…Coronavirus Disease-19 (COVID-19) is caused by Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) [ 1 ]. However, information about pediatric patients, especially those under 90 days of age, remains fragmented, scarce, and often contradictory [ 2 , 3 , 4 ]. Knowledge of these young patients has been extrapolated from older pediatric cases, with a limited number of research and case series publications during the ongoing pandemic [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential risk factors for community-acquired COVID-19 in very young individuals are unclear, with speculation about whether immature immune systems pose a risk or play a protective role [ 2 , 5 , 6 , 7 , 8 ]. Several risk stratification scores for COVID-19 in young infants have been proposed but often show conflicting results, and the percentage of infants experiencing severe COVID-19 varies widely across different studies [ 1 , 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%